2024
DOI: 10.1021/acsnano.3c10412
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Precise Manufacturing of Silicon Electronics

Jason Pitters,
Jeremiah Croshaw,
Roshan Achal
et al.

Abstract: Atomically precise manufacturing (APM) is a key technique that involves the direct control of atoms in order to manufacture products or components of products. It has been developed most successfully using scanning probe methods and has received particular attention for developing atom scale electronics with a focus on silicon-based systems. This review captures the development of silicon atom-based electronics and is divided into several sections that will cover characterization and atom manipulation of silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 333 publications
(876 reference statements)
0
0
0
Order By: Relevance
“…Recent progresses in the atomically precise manipulation of TM atoms on substrates have demonstrated the feasibility of manufacturing atom-scale spintronic devices. [16,17] It has been revealed that TM atoms on ultrathin MgO(100) layers deposited on Ag(100) substrates, denoted as MgO(100)/Ag(100), show intriguing magnetic properties. For instance, a single Co atom on MgO(100)/Ag(100) achieved the magnetic anisotropy limit; [11] an isolated Fe atom on MgO(100)/Ag(100) manifested strong perpendicular magnetic anisotropy with the largest reported magnetic anisotropy energy (MAE) for Fe atoms adsorbed on surfaces; [12] an individual Ho atom on MgO(100)/Ag(100) exhibited a long relax-ation time of magnetic remanence.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progresses in the atomically precise manipulation of TM atoms on substrates have demonstrated the feasibility of manufacturing atom-scale spintronic devices. [16,17] It has been revealed that TM atoms on ultrathin MgO(100) layers deposited on Ag(100) substrates, denoted as MgO(100)/Ag(100), show intriguing magnetic properties. For instance, a single Co atom on MgO(100)/Ag(100) achieved the magnetic anisotropy limit; [11] an isolated Fe atom on MgO(100)/Ag(100) manifested strong perpendicular magnetic anisotropy with the largest reported magnetic anisotropy energy (MAE) for Fe atoms adsorbed on surfaces; [12] an individual Ho atom on MgO(100)/Ag(100) exhibited a long relax-ation time of magnetic remanence.…”
Section: Introductionmentioning
confidence: 99%